Uraniferous pegmatites in the Grease River area, northern Saskatchewan ... - Costaschuk, Suzanne Mickey (University of Alberta Library, 1979)
Studies the geology and uranium mineralization of the area bordering the Grease River in the Fond-du-Lac area. ...